Tenaga Hibrid (Angin dan Surya) di Pantai Baru Pandansimo Bantul Yogyakarta - Tri Suhartanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2014)
Renewable energy sources is a solution of alternative energy to overcome the electricity crisis in Indonesia. Hybrid Power Plant at Baru Padansimo beach, Bantul, Yogyakarta, is the pilot project of Hybrid energy based on potentials of solar energy and wind power which used as models in the developement of renewable energy in integrated manner through Regional Inovation System. Performance of a hybrid power system can be evaluated from reliability system and economic aspects. In general, integration on Hybrid Power Plant system is a multivariable system, so to model the hybrid system, a 2.68 version of HOMER (Hybrid Optimization Model for Electric Renewables) software is needed. This software optimizes the design of Hybrid Power Plant system based on the lowest NPC value with estimated measurements or system capacity and costs as outputs. Pandansimo Hybrid Power Plant system configuration consists of PLTS and PLTB. The analysis of Pandansimo Hybrid Power Plant system is done through two systems modeling Off-Grid and On-Grid. First, the results of the analysis indicate that the Hybrid Power Palnt system is feasible in meeting the needs of users of electrical energy based on the total net present value (NPC) of U.S. 307,302, generating cost (COE) of U.S. 0.872 per kWh, electricity production capacity of 121, 239 kWh per year, and the excess of electricity during the year amounted to 94 705 kWh. Second, the configuration of Hybrid Power Plant system On-Grid can improve the effectiveness of Pandansimo Hybrid Power Plant in the utilization of renewable energy sources as to reduce the NPC to U.S. 253,850, at a cost of U.S. 0.720 COE. The ability of selling electricity at 94,705 kWh per year. Configuration system to grid can also reduce network’s CO2 emissions by 31,557 pounds per year.